Infections with highly pathogenic avian influenza A virus (HPAIV) H5N8 in harbor seals at the German North Sea coast, 2021. Issue 1 (31st December 2022) - Postel, Alexander; King, Jacqueline; Kaiser, Franziska K.; Kennedy, Johanna; Lombardo, Mara Sophie; Reineking, Wencke; de le Roi, Madeleine; Harder, Timm; Pohlmann, Anne; Gerlach, Thomas; Rimmelzwaan, Guus; Rohner, Simon; et al.
ABSTRACT: In brain tissue of three harbor seals of the German North Sea coast, high virus loads of highly pathogenic avian influenza virus (HPAIV) H5N8 were detected. Identification of different virus variants indicates high exposure to HPAIV circulating in wild birds, but there is no evidence for H5 specific antibodies in healthy seals. Replication of avian viruses in seals may allow HPAIV to acquire mutations needed to adapt to mammalian hosts as shown by PB2 627K variants detected in these cases.